A new mid-altitude rainforest species of Typhlops (Serpentes: Typhlopidae) from Madagascar with notes on the taxonomic status of T. boettgeri Boulenger, T. microcephalus Werner, and T. capensis Rendahl - Wallach, Van; Glaw, Frank (Zootaxa, 2009)
We describe a new Typhlops species from mid-altitude rainforest (ca. 950 m elevation) of the Andasibe region in central eastern Madagascar. Typhlops andasibensis sp. nov. is a medium-sized species (up to 340 mm total length) and can be separated from all other Malagasy typhlopids by the combination of 26 midbody scale rows, less than 400 middorsals, and a T–V supralabial imbrication pattern. Typhlops microcephalus is confirmed as a valid species, T. boettgeri is resurrected from the synonymy of T. arenarius, and T. capensis is synonymized with Ramphotyphlops exocoeti. Keys to the three genera and 14 described species of Madagascar and Comoro typhlopids are provided.